An estimation of sediment yield using universal soil loss (USLE) and rating curve in Barat Daya District of Penang, Malaysia - Mohd Najib, Sumayyah Aimi; A. Rahaman, Zullyadini (2015)

(untitled)
Sediment yield estimation in rivers at the regional or local scale is very important especially in term of managing the water resources in the catchment area. The sediment yield usually calculated either from direct measurement of sediment concentration in rivers or from sediment transport equation at a particular outlet point in the catchment. A total of 19 rivers were selected as sampling sites located at the Barat Daya District of Penang. The Universal Soil Loss Equation (USLE) was used to estimate the sediment yield in the study area by integrating with the Geographic Information System (GIS) to generate maps of the USLE factors, which are rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), crop management (C), and conservation practice (P) factors. A sediment rating curves of the study area was developed to verify the accuracy as well as comparison to the sediment yield estimated by USLE. The results show good correlation between the sediment yield estimated by USLE and observed data (r2 is 0.62). The sediment yield estimated in the year 1974 was 1300 ton/km2/year, 1984 was 1921 ton/km2/year, 2004 was 1919 ton/km2/year and 2012 was 2336 ton/km2/year. Based on the land use analysis, agricultural activity was dominant in the Barat Daya area and contributes much of the sediment into the river system.